Evaluation of Office Chairs to Enhance Comfort and Reduce Musculoskeletal Risk in Sedentary Work Environments - Fitrianto, Taufik Ramadhan; Prakoso, Galih; Nugroho, Alfani Risman; Afifah, Anshah Silmi; Anggiriani, Siska; Widiastuti, Retno (Institut Teknologi Adhi Tama Surabaya, 2025)
This study evaluates the effectiveness of an ergonomically redesigned office chair, tailored to meet the anthropometric needs of employees. It addresses common issues associated with prolonged sitting, such as musculoskeletal discomfort and fatigue, which are prevalent in sedentary work environments. Utilizing anthropometric data from prior studies, the redesign incorporates modifications in key chair dimensions—such as seat height, seat depth, and backrest height—to enhance user comfort and reduce physical strain. The ROSA (Rapid Office Strain Assessment) tool was employed to assess posture and ergonomic risk for both the old and redesigned chairs. Findings indicate a significant improvement in ergonomic support and comfort with the new design, supported by a statistically significant reduction in ROSA scores, as confirmed through a paired sample t-test. Although the redesign effectively enhances comfort, further improvements are recommended, including adjustable lumbar support and backrest flexibility. This study underscores the importance of ergonomic adaptations in office furniture to support diverse body types and reduce occupational health risks.